The Impact of the Crisis of the Soviet State in the 80s of the XX Century on the National Economy and Agriculture of Uzbekistan - Khurshida Erkinovna, Yunusova; Umidjon Abdumavlyanovich, Usarov; Akmal Yaxshiboevich, Mamatkulov; Nurbek Abdigapporovich, Tolibov (International Journal of Psychosocial Rehabilitation, 2020)
The last two decades of the twentieth century were one of the most difficult in the history of the Soviet Union, one of the largest empires in the world, and were a period of responsible turning. During these years, the command-and-control method of governance continued until the Soviet government, which had kept the socioeconomic situation within a certain framework, abandoned free market relations and chose the path of extensive development of the socialist economy. The use of the achievements of the national economy in the fields of science, engineering, and technology and the application of the experience of developed countries also faced serious obstacles associated with the administration. In the 1980s, spending in the country increased so much that the country became a site of "huge construction." The fight against alcoholism has intensified. At the same time, the Soviet government, which had no choice but to strengthen ties with the socialist countries, continued to strengthen ties with such countries at the expense of financial resources. As a result of such inefficient production relations, the country, which has accumulated the most fertile lands in the world, has become mired in economic crises, unable to provide its population with food and light industry products. The processes that took place in the country, in turn, were difficult in the allied republics. Influencing the structure of industry in Uzbekistan, which is part of the Central Asian economic region, cotton growing required the development of enterprises for the production of mineral fertilizers, cotton ginning, textile and industry machinery and equipment, and agricultural machinery. Agriculture was also in a state of economic crisis, and excessive attention to raw cotton did not cover the costs incurred for agriculture, and real incomes from agriculture remained incomplete. This situation, even in the 1980s, allowed the strengthening of the economic monopoly by managing the national economy on the basis of a centralized plan.